Fractal model of thermal contact conductance of two spherical joint surfaces considering friction coefficient. Issue 1 (3rd January 2022) - Sun, Xianguang; Meng, Chunxiao; Duan, Tiantang
Abstract : Purpose: The purpose of this study is to propose a fractal model of thermal contact conductance (TCC) of two spherical joint surfaces, considering friction coefficient based on the three-dimensional fractal theory. Design/methodology/approach: The effects of friction coefficient, fractal parameters, radius of curvature and contact type on TCC were analyzed using numerical simulation. Findings: The results indicate that the TCC decreases with the increase of friction coefficient and fractal roughness and increases with the increase of fractal dimension and radius of curvature; the contact type of two spherical joint surfaces has an important influence on the TCC, and the TCC of external contact is smaller than that of internal contact under the same contact load. Originality/value: A fractal model of TCC of two spherical joint surfaces considering friction coefficient is proposed in this paper. Achievements of this work provide some theoretical basis for the research of TCC of bearings and other curved surfaces.